Population-based study in a rural area: methodology and challenges - Helen Gonçalves; Elaine Tomasi; Luciana Tovo-Rodrigues; Renata Moraes Bielemann; Adriana Kramer Fiala Machado; Ana Carolina Oliveira Ruivo; Caroline Cardozo Bortolotto; Gustavo Pêgas Jaeger; Mariana Otero Xavier; Mayra Pacheco Fernandes; Rafaela Costa Martins; Roberta Hirschmann; et al. (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To describe the planning, sampling, operational aspects of the field, and the sample obtained during a research conducted in a rural area, specifying and discussing the main logistical difficulties unique to these places and the solutions adopted. METHODS We carried out a population-based, cross-sectional survey between January and June 2016, with a representative sample of the population aged 18 years or over living in the rural area of Pelotas (approximately 22,000 individuals), State of Rio Grande do Sul, Brazil. We collected demographic, socioeconomic, and health-related information, such as alcohol consumption, cigarette consumption, depressive symptoms, quality of diet, quality of life, physical activity, satisfaction with the health unit, overweight or obesity, and sleep problems. RESULTS In the 720 domiciles sampled, 1,697 individuals were identified and 1,519 were interviewed (89.5%). The study initially drew 24 census tracts and proposed the visit to 42 households per tract; however, we need to adjust the method, such as decreasing the number of households per census tract (from 42 to 30) and identifying housing centers in each tract. The main reasons for these changes were difficulty accessing the area, large distances between households, misconceptions in the satellite data available (which did not fit the reality), and high cost of the field work. CONCLUSIONS The previous detailed recognition of the research environment was crucial for decision making as the maps and territory had geographical inconsistencies. The strategies and techniques used in studies for the urban area are not applicable to the rural area given the outcomes observed in Pelotas. The decisions taken, keeping the methodological rigor, were essential to ensure the timely execution of the study with the financial resources available.